No effects of dapagliflozin, metformin or exercise on plasma glucagon concentrations in individuals with prediabetes: A post hoc analysis from the randomized controlled PRE‐D trial. Issue 2 (18th November 2020) - Clemmensen, Kim K. B.; Blond, Martin B.; Amadid, Hanan; Bruhn, Lea; Vistisen, Dorte; Karstoft, Kristian; Persson, Frederik; Ried‐Larsen, Mathias; Holst, Jens J.; Wewer Albrechtsen, Nicolai J.; Torekov, Signe S.; Quist, Jonas S.; et al.
Abstract: Aim: To assess the effects of dapagliflozin, metformin and exercise treatment on changes in plasma glucagon concentrations in individuals with overweight and HbA1c‐defined prediabetes. Materials and Methods: One‐hundred and twenty individuals with overweight (body mass index ≥ 25 kg/m 2 ) and prediabetes (HbA1c of 39‐47 mmol/mol) were randomized to a 13‐week intervention with dapagliflozin (10 mg once daily), metformin (850 mg twice daily), exercise (30 minutes of interval training 5 days per week) or control (habitual living). A 75‐g oral glucose tolerance test (OGTT) (0, 30, 60 and 120 minutes) was administered at baseline, at 13 weeks (end of intervention) and at 26 weeks (end of follow‐up). Linear mixed effects models with participant‐specific random intercepts were used to investigate associations of the interventions with fasting plasma glucagon concentration, insulin/glucagon ratio and glucagon suppression during the OGTT. Results: At baseline, the median (Q1; Q3) age was 62 (54; 68) years, median fasting plasma glucagon concentration was 11 (7; 15) pmol/L, mean (SD) HbA1c was 40.9 (2.3) mmol/mol and 56% were women. Compared with the control group, fasting glucagon did not change in any of the groups from baseline to the end of the intervention (dapagliflozin group: −5% [95% CI: −29; 26]; exercise group: −8% [95% CI: −31; 24]; metformin group: −2% [95% CI: −27; 30]). Likewise, there were no differences in insulin/glucagon ratio and glucagon suppression during the OGTT between the groups. Conclusions: In individuals with prediabetes, 13 weeks of treatment with dapagliflozin, metformin or exercise was not associated with changes in fasting or post‐OGTT glucagon concentrations.